ANALISIS PEMBENTUKAN KARAKTER KEMANDIRIAN PADA PEMBELAJARAN MATEMATIKA MODEL SAVI BERBASIS DISCOVERY STRATEGY - Handoko, Hendri (Integral : Pendidikan Matematika, 2023)
Abstract Learning mathematics in three-dimensional material often experiences difficulties, one of the factors causing this is the low level of student independence in learning. One of the alternatives provided to solve this problem is by determining innovative learning strategies. One of the innovative learning methods that will be used as an alternative to overcome this problem is the SAVI learning model based on discovery strategies, which is defined as a teaching technique that involves all students' senses in searching for and discovering a mathematical concept. This learning activity focuses students on the process of discovering a mathematical concept. The aim of this research is to analyze the results of the process that has an impact on the formation of students' independent character in learning three-dimensional mathematics material using the SAVI model approach based on discovery strategy. The research subjects were taken from 6 students who had different abilities (heterogeneous), namely by grouping the upper (high ability), middle (medium group), and lower (lower group). Data collection techniques are obtained by observation, interviews, documentation. The instruments used were observation sheets and interview guidelines, documentation. Meanwhile, data processing techniques use gain and triangulation tests. The results of observations of independence in this study showed that the average increase in the character of independence from meetings I to V in the selected subjects was 78.40, meaning an increase in the formation of good criteria. Keywords: Independence, SAVI Learning Model, Discovery Strategy Abstrak Pembelajaran matematika materi dimensi tiga sering mengalami kesulitan, salah satu faktor penyebabnya adalah karena rendahnya kemandirian siswa dalam belajar. Salah satu alternatif yang diberikan untuk menyelesaikan permasalahan tersebut adalah dengan cara menentukan strategi pembelajaran yang inovatif. Salah satu pembelajaran inovatif yang akan dijadikan alternatif untuk mengatasi permasalahan tersebut yaitu pembelajaran model SAVI berbasis discovery strategy yang diartikan sebagai teknik pengajaran yang melibatkan semua indera siswa dalam mencari dan menemukan suatu konsep matematika. Kegiatan pembelajaran ini memfokuskan siswa pada proses penemuan suatu konsep matematika. Tujuan dari penelitian ini adalah untuk menganalisis hasil dari proses yang berdampak pada pembentukan karakter kemandirian siswa pada pembelajaran matematika materi dimensi tiga dengan pendekatan model SAVI berbasis discovery strategy. Subjek penelitian diambil dari 6 siswa yang memiliki kemampuan yang berbeda (heterogen) yaitu dengan pengelompokan kelompok atas (kemampuan tinggi), tengah (kelompok sedang), dan bawah (kelompok bawah). Teknik Pengambilan data diperoleh dengan observasi, wawancara, dokumentasi. Instrumen yang digunakan lembar observasi dan pedoman wawancara, dokumentasi. Sedangkan teknik pengolahan data dengan uji gain dan triangulasi. Hasil pengamatan kemandirian pada penelitian ini menunjukan bahwa rata-rata peningkatan karakter kemandirian dari pertemuan I sampai V pada subjek terpilih dihasilkan sebesar 78,40 artinya peningkatan pembentukan pada kriteria baik. Kata kunci: Kemandirian, Model Pembelajaran SAVI, Discovery Strategy